Water quality management in aquaculture - Fatimah M. Yusoff; Wahidah A. D. Umi; Norulhuda M. Ramli; Razif Harun (Cambridge Prisms: Water, 2024)
The aquaculture industry requires good water quality for its successful operation but produces wastes that can cause environmental deterioration and pose high risks to the sector. Adequate waste treatment and recycling are necessary to make aquaculture a sustainable and profitable industry and contribute to the circular economy. Polluted water sources, excess feeding, overstocking, use of antibiotics/chemicals and harmful algal blooms are major causes of water quality deterioration and low production in aquaculture systems. Discharges of untreated wastes would have serious impacts on the receiving water bodies, and eventually on the aquaculture industry itself. Possible solutions include technological innovations in environmentally friendly production systems, use of efficient processes in water quality management and improved legislation and governance. Environmentally feasible aquaculture production technologies such as recycling aquaculture system, integrated multi-trophic aquaculture and aquaponics including features of waste recycling are viable options in aquaculture schemes. Best aquaculture practices integrating advanced water quality treatment processes and technologies, supported by automation and sensors, modeling and artificial intelligence-internet of things are necessary for a sustainable aquaculture environment, production and stable value chain. In general, low-cost technologies for aquaculture waste treatment and environmental impact reduction through good governance are crucial for achieving sustainability in the aquaculture industry and natural environmental management.